2016
DOI: 10.5812/jjm.33639
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Gamma Gene Polymorphism (+874 T > A) and Chronic Hepatitis B in the Population of Gorgan, North-Eastern Iran

Abstract: BackgroundBased on differences in individual immune responses to the hepatitis B virus (HBV), between 5% and 10% of patients become persistently infected with the virus, which leads to the determination of chronic HBV. Cytokines such as interferon gamma (IFN-γ) are secretory proteins that play important roles in both innate and adaptive immune responses. Functional studies have demonstrated that the IFN + 874A/T gene polymorphism can increase or decrease the overall expression of IFN-gamma (γ) and ultimately d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
(35 reference statements)
2
8
0
Order By: Relevance
“…Also in agreement with our results, in a rural area of Northern China IFN-γ+ 874 AA genotype showed to be associated with an increased risk of chronic HBV infection [30]. On the other hand, a study from Iran in 2016 showed no association between this polymorphism and HBV clearance in a population from Golestan Province [31]. The difference in results might be attributed to the ethnic background of the studied populations, sample size, and the genotyping method.…”
Section: Discussionsupporting
confidence: 89%
“…Also in agreement with our results, in a rural area of Northern China IFN-γ+ 874 AA genotype showed to be associated with an increased risk of chronic HBV infection [30]. On the other hand, a study from Iran in 2016 showed no association between this polymorphism and HBV clearance in a population from Golestan Province [31]. The difference in results might be attributed to the ethnic background of the studied populations, sample size, and the genotyping method.…”
Section: Discussionsupporting
confidence: 89%
“…Polymorphisms in genes encoding cytokines may be the primary cause of clinical differences between patients; hence they can be used for the identification of individuals who are at high risk of developing hepatocellular carcinoma and chronic hepatitis (3,36). So far, we have evaluated the association of several genes with hepatitis and cancer (27,(47)(48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen articles met the inclusion criteria. [13][14][15][16][18][19][20][21][22][23][24][25][26] The literature selection process is shown in Figure 1. The characteristics of the included studies, genotype distribution frequency, and literature quality scores are shown in Table 1.…”
Section: Literature Retrievalmentioning
confidence: 99%
“…11 HBV infection levels were found to decrease with increasing IFN-c expression in chimpanzees, 12 so the susceptibility to HBV is thought to be associated with IFN-c gene SNPs. Yu et al 13 and Korachi et al 14 found that the T allele at IFN-c þ874 was a protective factor against HBV infection, Arababadi et al 15 reported that the T allele was not associated with HBV susceptibility, while Ghasemian et al 16 showed that it was a risk factor for HBV infection. Because the conclusions of these previous studies are inconsistent, we herein used a meta-analysis to investigate whether the IFN-c þ874 SNP is associated with susceptibility to HBV infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation